Review of Tess Knighton and Álvaro Torrente, eds. 2007. Devotional Music in the Iberian World, 1450-1800: The Villancico and Related Genres. Aldershot, UK, and Burlington, VT: Ashgate Publishing - Le Guin, Elisabeth (Current Musicology, 2009)
“Villancico” is a baggy term for an enormous range of related practices and genres, and as such, a good analogy to the equally baggy term “cantata”. Indeed, there was for a time a certain amount of crossover or fusion between the two terms in Spanish-speaking lands, as Juan Jose Carreras has pointed out. The huge range of time during which things called villancicos were produced, the large number of communities in which they appeared and the great variety of purposes that the therefore came to serve, all make it both urgent and impossible to define “the villancico”. So; a sprawling mess, a conundrum, an endlessly rich fund of musical practices and products, mingling devotional and secular, learned and popular, official and indigenous, complexities, overt and covert-the villancico is a genre emblematic of the impossible historical and cultural diversity of the Iberian Empires.